New insights into oculodermal nevogenesis and proposal for a new iris nevus classification. Issue 5 (30th October 2014) - Schwab, Christoph; Zalaudek, Iris; Mayer, Christoph; Riedl, Regina; Wackernagel, Werner; Juch, Herbert; Aigner, Birgit; Brunasso, Alexandra Maria; Langmann, Gerald; Richtig, Erika
Abstract : Background/aims: To gain more knowledge about presence and dermatological associations of iris nevi as well as possible pathways involved in the formation of iris nevi. Methods: We conducted a prospective, interdisciplinary observational study. Presence, morphology, topography of iris and cutaneous nevi as well as factors indicating sun-exposure were noted. Results: A total of 632 participants including 360 (57%) women were examined. Of those, 26 subjects revealed 27 iris nevi. According to the current classification, all iris nevi were judged as solitary with the majority of them (n=20; 74%) located in the lower quadrants. In six (22.2%) cases we noted a peculiar 'incomplete sectoral pattern'; these nevi were located close to the pupil, were larger and had a more elongated, triangular shape compared with those located distant from the pupil, which appeared smaller and more roundish. Notably, five of these six peculiar (incomplete sectoral) iris nevi were located on the upper half of the iris. Conclusions: Based on our findings we propose classifying iris nevi into sectoral, incomplete sectoral and solitary subtypes. Additionally, we set up a hypothetic concept of oculodermal nevogenesis suggesting a time-dependent embryogenic alteration affecting the normal melanocyte location, migration and maturation along peripheral nerve sheets. Our new concept explains well the morphology and extension of benign melanocytic proliferations in the ocular region as well as their relation to uveal melanoma.